2018
DOI: 10.1111/rda.13213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in testicular size, echotexture, and arterial blood flow associated with the attainment of puberty in Dorper rams raised in a subtropical climate

Abstract: There is a paucity of information on the relationships of testicular morphology, echotextural attributes, and blood flow dynamics with pubertal development of rams raised in a subtropical climate. Forty-five Dorper rams (24 rams aged 8-11 months and 21 rams aged 12-24 months) were examined using a portable ultrasound scanner connected to a 7.5-MHz transducer. Computer-assisted analyses of testicular ultrasonograms utilized commercially available Image ProPlus analytical software. Spectral Doppler scans of test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
34
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 44 publications
9
34
0
4
Order By: Relevance
“…In the present study there were no significant differences between the LTA and RTA with respect to all blood flow parameters PI, RI and PSV, Thus, the means of both the LTA and RTA arteries were used for further analysis of these variables. Similar results were recorded in arterial blood flow parameters (PSV, end-diastolic velocity; RI and PI) associated with the attainment of puberty in Dorper rams raised in a subtropical climate (Camela et al, 2018). On the other hand, the effect of laterality on the testicular hemodynamics has been recently studied by Hedia et al, (2020) who found that Doppler indices of RI and PI were slightly higher in the RTA rather than the LTA in rams…”
supporting
confidence: 79%
“…In the present study there were no significant differences between the LTA and RTA with respect to all blood flow parameters PI, RI and PSV, Thus, the means of both the LTA and RTA arteries were used for further analysis of these variables. Similar results were recorded in arterial blood flow parameters (PSV, end-diastolic velocity; RI and PI) associated with the attainment of puberty in Dorper rams raised in a subtropical climate (Camela et al, 2018). On the other hand, the effect of laterality on the testicular hemodynamics has been recently studied by Hedia et al, (2020) who found that Doppler indices of RI and PI were slightly higher in the RTA rather than the LTA in rams…”
supporting
confidence: 79%
“…Camela et al. (2018) documented testicular echotexture differences in sheep with pre‐pubertal animals showing higher heterogeneity than post‐pubertal animals because of the various testicular histomorphology changes occurring after puberty, especially in the proliferative post‐mitotic phase of the cells forming the seminiferous tubules. The decrease in heterogeneity and sperm concentration increase is probably related to the rise in serum testosterone levels caused by omega‐3 supplementation (Santos et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers did not find a correlation between pixel intensity and sperm production or semen quality in dogs (Dias et al., 2017; Pinho et al., 2012; Tomlinson et al., 2017). Many researchers have reported that testicular echogenicity increases during sexual development directly with seminiferous tubules growth (Camela et al., 2018; Hamm & Fobbe, 1995; Pozor et al., 2017; Silva et al., 2012). It is plausible that increased or decreased testicular echogenicity represents ultrastructural changes within the testes associated with altered sperm morphology (Santos et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…gösterirler. İneklerde, iki östrus arasındaki hormonal ve üreme sistemindeki değişimleri kapsayan dönem östrus siklusu olarak adlandırılır (1)(2)(3)(4)(5). Östrus siklusunda, foliküler ve luteal fazın alt bölümlerini içeren dört dönem vardır.…”
unclassified
“…(12,19). Bilgisayar destekli görüntü analiz programları ile domuzlarda,(16) keçilerde(3,15), Avrupa karacalarında(11), köpeklerde (20) ve ineklerde(18) kullanılmaktadır. Bu yöntemle erken gebelik döneminde ve siklusta ineklerde endometriyal ve luteal değişiklikler belirlenebilmektedir(18).Erzurum ilinde bulunan özel bir çiftlikte yürütüldü.Çalışmada 1. laktasyondaki, 3 yaşlı, aynı bakım ve besleme şartlarında barındırılan, ortalama 18 litre günlük süt verimi olan 42 adet Holstein ırkı inek kullanıldı.…”
unclassified